2018
DOI: 10.1016/j.redox.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

PKR activation causes inflammation and MMP-13 secretion in human degenerated articular chondrocytes

Abstract: Osteoarthritis (OA) is a degenerative joint disease affecting a large population of people. Although the elevated expression of PKR (double stranded RNA-dependent protein kinase) and MMP-13 (collagenase-3) have been indicated to play pivotal roles in the pathogenesis of OA, the exact mechanism underlying the regulation of MMP-13 by PKR following inflammatory stimulation was relatively unknown. The purpose of this study was to determine the signaling pathway involved in the PKR-mediated induction of MMP-13 afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 51 publications
6
54
0
Order By: Relevance
“…Similarly, MMP-13, MMP-3, MMP-2, and MMP-9 increased in the cell line model of osteoarthritis [26,28]. Furthermore, several studies have investigated the MMP-13 level in osteoarthritis patients, and consistent observation is obtained, whereby the MMP-13 level increased significantly in patients with osteoarthritis [30,48,59,[73][74][75][76][77][78]. MMP-13, as a collagenase, is responsible for the degradation of type II collagen [79], which is the main collagen type in articular cartilage [80].…”
Section: The Role Of Matrix Metalloproteinases (Mmps) In Osteoarthritismentioning
confidence: 67%
“…Similarly, MMP-13, MMP-3, MMP-2, and MMP-9 increased in the cell line model of osteoarthritis [26,28]. Furthermore, several studies have investigated the MMP-13 level in osteoarthritis patients, and consistent observation is obtained, whereby the MMP-13 level increased significantly in patients with osteoarthritis [30,48,59,[73][74][75][76][77][78]. MMP-13, as a collagenase, is responsible for the degradation of type II collagen [79], which is the main collagen type in articular cartilage [80].…”
Section: The Role Of Matrix Metalloproteinases (Mmps) In Osteoarthritismentioning
confidence: 67%
“…Numerous studies reported increased levels of pPKR in damaged cartilages of OA patients 14,15,17 . Moreover, PKR activation was responsible for inflammation and MMP-13 secretion in degenerated articular chondrocytes 21 . The secretion of dsRNAs capable of activating TLR3 further supports the notion that PRRs are critical regulators during OA development.…”
Section: Discussionmentioning
confidence: 99%
“…Even though OA has been considered a non-inflammatory arthropathy, numerous proinflammatory cytokines play a role in the pathogenesis where they may drive the induction of MMPs and ADAMs 20 . Recently, studies have shown that pattern recognition receptors (PRRs) such as toll-like receptor 3 (TLR3) and PKR are involved as upstream regulators that induce the expression of cytokines 21,22 . Indeed, the increased level of pPKR was reported in damaged chondrocytes, and dsRNAs released from damaged chondrocytes induced TLR3 activation to promote cartilage degeneration 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, MMP-13 was known to function as an extracellular matrix (ECM)-degrading enzyme in OA joints. 15,16 In clinical samples, MMP-13 was abnormally expressed during different stages of OA process and was found to up-regulated during the early stage and down-regulated during the late stage in human OA cartilage, which indicated its central node in the cartilage degradation network and contribution of MMP-13 to the initiation/ onset of OA. 17,18 In addition, the activity of MMP-13 can be regulated at multiple levels, including epigenetic modification, transcriptional regulation and post-transcriptional regulation by ncRNAs.…”
Section: Introductionmentioning
confidence: 98%
“…Among these MMPs, MMP‐13 has caught a lot of attention in that it was significantly overexpressed in both joints and articular cartilage in OA patients and could hardly be detected in normal tissues. Besides, MMP‐13 was known to function as an extracellular matrix (ECM)‐degrading enzyme in OA joints . In clinical samples, MMP‐13 was abnormally expressed during different stages of OA process and was found to up‐regulated during the early stage and down‐regulated during the late stage in human OA cartilage, which indicated its central node in the cartilage degradation network and contribution of MMP‐13 to the initiation/onset of OA .…”
Section: Introductionmentioning
confidence: 99%